Assuring Quality in E-Learning Course Design: The Roadmap - Vlachopoulos, Dimitrios (International Review of Research in Open and Distributed Learning, 2016)
Quality Assurance (QA) concepts and applications in Higher Education (HE) emerge from evolving meanings related to HE’s dynamic relationship with social, economic, cultural, and technological developments. The latter has been redefined by the growth spurred by the forms distance and online education acquired during the last decades. Creating a roadmap with clearly articulated meanings of quality and consistent key actions fills a need for the involved communities to reground the research, policy-making, and the related discourse. Our current work consists of a thorough meta-analysis on all available research in every identified pertinent field. It is a qualitative review of the concepts, definitions, and approaches about quality in general, but also specifically, in e-learning in HE, as they have globally appeared in peer-reviewed journals, government reports, and web pages. As we left no stone unturned in enquiring regarding the meanings, uses, evolution, and applicability of the revealed variables it is our hope that the roadmap we provide here will guide future research and support policy-making in the field. The present study is part of the research project e-learning Quality Assurance Design Standards in Higher Education (e-QADeSHE), which was funded by Laureate International Universities as the winning research project for the International David Wilson Award for Excellence in Teaching and Learning (2015 edition).